Exploring Correlations between Molecular Topological Indices and X-ray Absorption Shifts in Cobalt (II) Complexes - Khatri, Sunil; Kekre, Pravin A; Mishra, Ashutosh (Current Research Progress in Physical Science Vol. 6, 2024)
This study established a correlation between X-ray absorption parameters like chemical shift with Randic and Schultz index respectively. The properties of a molecular system are affected by the topology of the molecule. Therefore, many studies have been made where the various physic-chemical properties are correlated with the topological indices. These studies have shown a very good correlation demonstrating the utility of the graph theoretical approach. It is, therefore, very natural to expect that the various physical properties obtained by the X-ray absorption spectra may also show a correlation with the topological indices. Some complexes were used to establish a correlation between topological indices and some X-ray absorption parameters like chemical shift. The chemical shift is on the higher energy side of the metal edge in these complexes. The study showed that the correlations with the Schultz Index are better than those with the Randic Index. The result obtained in these studies shows that the topological indices of the organic molecule acting as a ligand can be used for estimating edge shift theoretically. The topological understanding of molecular properties can lead to the development of new areas of present and future interest i.e. tracking the effect of pollutants in the environment, designing drugs and predicting of carcinogenicity of molecules.